2020
DOI: 10.1073/pnas.1920021117
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar localization of RAG1 modulates V(D)J recombination activity

Abstract: V(D)J recombination assembles and diversifies Ig and T cell receptor genes in developing B and T lymphocytes. The reaction is initiated by the RAG1-RAG2 protein complex which binds and cleaves at discrete gene segments in the antigen receptor loci. To identify mechanisms that regulate V(D)J recombination, we used proximity-dependent biotin identification to analyze the interactomes of full-length and truncated forms of RAG1 in pre-B cells. This revealed an association of RAG1 with numerous nucleolar proteins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 66 publications
(76 reference statements)
1
31
1
Order By: Relevance
“…We statistically evaluated the dynamic enrichment of these 600 RBPs with each of the evaluated ribosomal complexes between steady state and upon translational challenge and ranked them based on preferential enrichment upon stress (Hoteling's Two Sample T2) Figure 1E, Table S1). The top five enriched RBPs were BZW1 (Kozel et al, 2016), AARS (Negrutskii and Deutscher, 1991), HMGB2 (Leppek et al, 2021), RBPMS, and KNOP1, of which all except RBPMS and KNOP1 (KNOP1 is reported to be in the nucleolus (Brecht et al, 2020)) are known regulators of translation, consolidating that our identification and prioritization criteria yield translational regulators. While RBPMS has never been reported as a regulator of translation, it has been suggested as a potential regulator of embryogenesis (Aguero et al, 2016;Gerber et al, 2002;Gerber et al, 1999).…”
Section: Rna Binding Protein Rbpms Is a Translation Machinery-associamentioning
confidence: 77%
See 1 more Smart Citation
“…We statistically evaluated the dynamic enrichment of these 600 RBPs with each of the evaluated ribosomal complexes between steady state and upon translational challenge and ranked them based on preferential enrichment upon stress (Hoteling's Two Sample T2) Figure 1E, Table S1). The top five enriched RBPs were BZW1 (Kozel et al, 2016), AARS (Negrutskii and Deutscher, 1991), HMGB2 (Leppek et al, 2021), RBPMS, and KNOP1, of which all except RBPMS and KNOP1 (KNOP1 is reported to be in the nucleolus (Brecht et al, 2020)) are known regulators of translation, consolidating that our identification and prioritization criteria yield translational regulators. While RBPMS has never been reported as a regulator of translation, it has been suggested as a potential regulator of embryogenesis (Aguero et al, 2016;Gerber et al, 2002;Gerber et al, 1999).…”
Section: Rna Binding Protein Rbpms Is a Translation Machinery-associamentioning
confidence: 77%
“…The top-ranking candidate TSF, RNA binding protein RBPMS (RNA-Binding Protein with Multiple Splicing) was selected for further analysis. Notably, the top five enriched RBPs were BZW1 40 , AARS 41 , HMGB2 42 , RBPMS, and KNOP1, of which all except RBPMS and KNOP1 (KNOP1 has been reported to be in the nucleolus 43 ) are known regulators of translation, consolidating that our prioritization criteria do identify translational regulators. RBPMS is an evolutionarily conserved, but poorly characterized RBP suggested as a regulator of embryogenesis 44-46 .…”
Section: Unprecedented Diversity Of Proteins Residing On Ribosomal Comentioning
confidence: 78%
“…Second, disruption of the HR pathway through the interruption of some components, such as ATR (Stortz et al, 2017;Black et al, 2020;Marin et al, 2020), Rad51 (McCulloch andProudfoot and McCulloch, 2005), Rad50 (Mehnert et al, 2021), and BRCA2 (Hartley and McCulloch, 2008), impairs the VSG switching by recombination, suggesting that multiple components are shared between these two pathways. In general, these features mirror targeted gene rearrangements in other organisms, such as VAR genes diversity in Plasmodium (Kyes et al, 2007;Claessens et al, 2014), pilin antigenic variation in Neisseria (Cahoon and Seifert, 2011), and V(D)J recombination during the development of B lymphocytes of the vertebrate immune system (Tonegawa, 1983;Brecht et al, 2020).…”
Section: The Role Of Dsbs In the Evasion Of T Brucei From The Host Immentioning
confidence: 87%
“…This phenomenon was termed nucleolar sequestration, which is now known to be an important mechanism for controlling gene expression and maintaining cellular homeostasis [ 35 , 36 , 37 ]. For example, dynamic nucleolar sequestration of RAG-1 has recently been shown to be a negative regulatory mechanism in V(D)J recombination [ 38 ]. MDM2 is sequestered in nucleoli in response to cellular stress, which prevents p53 degradation and consequently promotes cell cycle arrest and apoptosis (see below for details of this canonical nucleolar stress response pathway) [ 39 , 40 ].…”
Section: Regulation Of Apoptosis By Nucleolar Sequestration Of Nf-κb/relamentioning
confidence: 99%